The Influence of Organic‐Film Morphology on the Efficient Electron Transfer at Passivated Polymer‐Modified Electrodes to which Nanoparticles are Attached. Issue 10 (12th April 2013) - Barfidokht, Abbas; Ciampi, Simone; Luais, Erwann; Darwish, Nadim; Gooding, J. Justin
Abstract The impact of polymer‐film morphology on the electron‐transfer process at electrode/organic insulator/nanomaterial architectures is studied. The experimental data are discussed in the context of the most recent theory modelling the nanoparticle‐mediated electron‐transfer process at electrode/insulator/nanomaterial architectures proposed by Chazalviel and Allongue [J. Am. Chem. Soc.2011, 133, 762–764]. A previous report [Anal. Chem.2013, 85, 1073–1080] by us qualitatively verified the theory and demonstrates a transition from thickness‐independent to thickness‐dependent electron transfer as the layer thickness exceeds a certain threshold. This follow‐up study explores a different polymer, poly(phenylenediamine), and focuses on the effect of the uniformity of organic film on electron transfer at these hybrid structures. Electron‐transfer kinetics of modified surfaces, which were assessed using the redox species Ru(NH3)63+ in aqueous solution, showed that a thickness‐dependent electron‐transfer regime is achieved with poly(phenylenediamine). This is attributed to the sufficiently thin films never being fabricated with this polymer. Rather, it is suggested that thin poly(phenylenediamine) layers have a globular structure with poor film homogeneity and pinhole defects.